One-Pot Production of Tagatose Using L-Arabinose Isomerase from Thermotoga Maritima and β-galactosidase from Aspergillus Oryzae - Arenas-Salinas, F; Vera-Vera, C (Academic Press, 2024)
The one-pot production of tagatose from lactose using recombinant L-arabinose isomerase (L-AI) from Thermotoga maritima and commercial β-galactosidase (β-gal) from Aspergillus oryzae was evaluated. The β-gal and L-AI ratio (R β-gal/L-AI), initial lactose concentration and temperature were chosen as study variables. Maximum values of tagatose yield (YTag), specific tagatose productivity (πTag) and sugars ratio (RTag/Gal) obtained were 23 %, 0.202 ± 0.03 mmol Tag/(g prot⋅h) and 1, respectively. The composition of the product on a dry basis was as follows (g/g): 0.23 tagatose, 0.232 galactose, 0.454 glucose, 0.043 fructose, 0.029 lactose and 0.012 GOS. The one-pot production was superior compared with a sequential operation, where values of 16.5 %, 0.11 mmol Tag/(g prot⋅h) and 0.59 were obtained for YTag, πTag and RTag/Gal, respectively. © 2024